Pengembangan Media Pembelajaran Berbasis Android untuk Siswa Teknik Ketrampilan Kendaraan Ringan SMK - alfat khaharsyah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
This article aims to: (1) Create an android-based learning media that is used by students in the learning process of Light Vehicle Engineering expertise in SMK Negeri 2 Pengasih (SMK Negeri 2 Pengasih); (2) evaluating the feasibility of developed learning media; (3) describe the level of effectiveness of Android-based learning media products developed. This article can be categorized as Development of learning media which adopts the ADDIE development model including analysis, design, development, implementation, and evaluation. The stages of product development consist of analysis, design, development, implementation and evaluation. Product trials consist of internal trials and external trials. Data from the trial results were collected by questionnaire, field observations, and documentation. The article instruments are questionnaires, learning media in the form of Application Package (APK) files, and documents. The subject of this article was 46 students of Light Vehicle Engineering expertise at the 2 Loving Public Vocational School, with two instrument validators, two product validators, and two teachers. The results of the article were analyzed qualitatively and quantitatively. The findings show that (1) Product development, in the form of an Android-based learning media, contains several menus, such as, top right corner menu, description menu, theoretical menu, and exercise menu. (2) The feasibility level of android-based learning media from material experts can be categorized as "good" while those from media experts are declared "good" and the eligibility test for students is indicated in the "good" category. (3) The level of effectiveness of Android-based learning media application products obtained an N-gain of 76.09 (effective).